Sustainability practice in Local Government Engineering Department (LGED), Bangladesh: a case study on Tongibari upazila, Munshiganj - Parvez, Md. Rasel (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.